Top market strategy : applying the 80/20 rule - Kruger, Elizabeth Rush. (New York : Business Expert Press, 2011)
Research verifies that the 80/20 rule summarizes the stable relationship of inputs to outputs-- including the impact of customers on the profit of a business. According to this universal law, a business can predict that the most profitable 20% of its customers generates 80% of its profit from customers and that customers in this top market segment are 16 times more profitable than customers in the bottom market segment. Thus when a business replaces all customers in the bottom market segment with new customers in the top market segment, the business can expect to quadruple its profit from customers.
Marketing fundamentals -- Essentials of marketing -- Decisions about customer surveys -- The 80/20 rule -- The Pareto distribution -- Applications of the 80/20 rule -- Application to profit from customers -- Segmentation by profit from customers -- Steps of profitability segmentation -- How to increase profit from customers -- Interview diverse customers -- Create the customer survey -- Survey customers and analyze responses -- Define the profitability segments -- Distinguish the top market segment -- Evaluate and target the top market segment -- Create research-driven marketing strategies -- Quadruple profit from customers -- Appendix 1. Report on overall JetSpray customers -- Appendix 2. Report on JetSpray's top market segment -- Appendix 3. How to analyze overall customers -- Appendix 4. How to segment customers by profitability -- Appendix 5. How to profile a target market -- Appendix 6. Data worksheet in Microsoft Excel.
Includes bibliographical references (p. [109]) and index.
Keywords: Market segmentation; Market surveys; Marketing -- Management